Towards near-permanent CoCrMo prosthesis surface by combining micro-texturing and low temperature plasma carburising - Dong, Yangchun; Svoboda, Petr; Vrbka, Martin; Kostal, David; Urban, Filip; Cizek, Jan; Roupcova, Pavla; Dong, Hanshan; Krupka, Ivan; Hartl, Martin (Journal of the mechanical behavior of biomedical materials, 2015)
An advanced surface engineering process combining micro-texture with a plasma carburising process was produced on CoCrMo femoral head, and their tribological properties were evaluated by the cutting-edge pendulum hip joint simulator coupled with thin film colorimetric interferometry. FESEM and GDOES showed that precipitation-free C S-phase with a uniform case depth of 10μm was formed across the micro-textures after duplex treatment. Hip simulator tests showed that the friction coefficient was reduced by 20% for micro-metre sized texture, and the long-term tribological property of microtexture was enhanced by the C-supersaturated crystalline microstructure formed on the surface of duplex treated CoCrMo, thereby enhancing biotribological durability significantly. In-situ colorimetric interferometry confirmed that the maximum film thickness around texture area was 530nm, indicating that the additional lubricant during sliding motion might provide exceptional bearing life.
Keywords: Engineering; Feasibility Studies; Wear; kyčelní protézy; vysoká teplota; inženýrství; povrchové vlastnosti; Hot Temperature; Vitallium; Colorimetric interferometry; tření; mechanické jevy; studie proveditelnosti; Biotribology; vitalium; Mechanical Phenomena; Surface texturing; Friction; Surface Properties; plazmové plyny; Hip Prosthesis; Plasma Gases; Plasma carburising